Examining How Mobile Application User Experience, Service Quality, and Social Interaction Affect Customer Satisfaction: A Quantitative Study in the Online Services Industry - Abdullah Samad (Kalam Practica Media, 2025)
This study aims to analyze the influence of Mobile Application User Experience (MAUE), Service Quality (SQ), and Social Interaction (SI) on Customer Satisfaction (CS) in the online service industry. This study uses a quantitative approach with a survey method, where data is collected from 100 respondents who use online service applications. Data are analyzed using multiple linear regression tests to identify the relationship between independent variables and dependent variables. The results of the study indicate that the three independent variables have a positive and significant influence on customer satisfaction. The MAUE variable has the greatest influence with a coefficient value of 0.516, followed by SI with a coefficient of 0.223, and SQ with a coefficient of 0.182. The R² value of 0.614 indicates that 61.4% of the variation in customer satisfaction can be explained by this model. These findings support the theory of the Technology Acceptance Model (TAM) and SERVQUAL, and emphasize the importance of application experience, service quality, and social interaction in creating customer satisfaction. This study provides theoretical contributions to the existing literature and practical implications for companies to improve customer satisfaction through application development, service quality, and social interaction features.